JAMUR MAKROSKOPIS PADA TANDAN KOSONG KELAPA SAWIT DI KEBUN KELAPA SAWIT DESA TAWIORA, KECAMATAN RIO PAKAVA, KABUPATEN DONGGALA - Slamet Mardiyanto Rahayu; M. Ali Azis Hasan Rizki; Syuhriatin, Syuhriatin (Yayasan Nusantara Hasana Berdikari, 2025)
Empty Oil Palm Fruit Bunches (EFB) or empty bunches are organic waste produced from the processing of fresh oil palm fruit bunches into crude palm oil (CPO). EFB can be a growing medium for macroscopic fungi. This study aims to determine macroscopic fungi in EFB in the oil palm plantation of Tawiora Village, Rio Pakava District, Donggala Regency, Central Sulawesi Province. The study was conducted using exploration and identification methods based on the morphological characteristics of macroscopic fungi. Based on the study, there is one genus of macroscopic fungi in the oil palm plantation of Tawiora Village, namely: Volvariella. Volvariella has an umbrella-like shape, its hood is round egg-shaped which is then convex, the hood is brown to grayish brown, the stem is light brown, the cup is light brown with a membrane-like texture that forms a thick bowl, and the spore trail is pink.